A round robin study for laser beam melting in metal powder bed - Ahuja, Bhrigu (South African Journal of Industrial Engineering, 2016)
With its ability to fabricate fully dense three-dimensional structures by selectively melting micro-sized metal powder, the additive manufacturing process of laser beam melting (LBM) is considered by many to be a significant technology that is complementary to the conventional forming and subtractive manufacturing processes. However, even with its ability to fabricate structures with characteristics comparable to conventional fabrication, the LBM process often lacks the consistency and degree of repeatability essential for its industrial acceptance for certain end-product applications. Inconsistency in the characteristics of structures is often related to a combination of variations in system technology, process, and user influence. In order to understand fully the potential and limitations of the LBM process, the paper discusses the design, methodology, and results of a round robin test conducted within the Collaborative Working Group (CWG) lasers in production at the International Academy of Production Engineering (CIRP). Observed mechanical characteristics for samples from each of the participants are presented. The experiments are designed to obtain data related to mechanical characteristics for different build orientations and processing conditions in addition to the inherent system technology variations. The paper further discusses the observed process phenomena and their association with the induced mechanical characteristics.